Evaluating serum level of granulocyte, macrophage and granulocyte-macrophage colony-stimulating factors in patients with breast tumor: Serum level of G-CSF, M-CSF, and GM-CSF in breast tumor - Xin, Liu; Zhiyuan, Xu (Cellular and Molecular Biology, 2022)
Colony-stimulating factors (CSFs) are glycoproteins that stimulate the proliferation and differentiation of hematopoietic progenitor cells in the bone marrow. But numerous studies have shown that these factors can stimulate the proliferation of non-hematopoietic cells, including cancer cells. Hence, in this study, Macrophage-CSF (M-CSF), macrophage-granulocyte CSF (GM-CSF), and granulocyte-SCF (G-CSF) were evaluated in the serum of patients with breast tumors and their relationship with pathological and paraclinical parameters of the disease. In this study, 62 patients with breast cancer who had not received any treatment and 54 healthy women who matched the age group with the patient group were included as a control group. After obtaining informed consent, 5ml of peripheral blood was taken from both groups, and their serum was isolated. Serum levels of the studied cytokines were measured by the cytokine-bead array method. Data were analyzed using SPSS18 software and a significance level of 0.05. The mean serum levels of M-CSF, G-CSF, and GM-CSF growth factors in patients with breast cancer were 63.48, 16.13, and 6.11pg/ml, respectively. Although the statistical analysis did not show a significant difference between serum levels of these growth factors in the patient and control groups (p <0.05), further studies showed that with increasing disease stages from I to III, serum levels of GM-CSF significantly. Decreases (p = 0.016). Overall, the results of this study indicated the antitumor role of GM-CSF in breast cancer. However, confirmation of these results requires more complete studies with larger sample sizes.